Analysis of Traffic Accidents Using the Accident Rate Method (Case Study: MT. Haryono Street – Gatot Subroto Street South Jakarta City) - Kusumaningrum, Riandha; Widyaningsih, Nunung (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
MT. Haryono - Gatot Subroto Street South Jakarta is one of the arterial roads in the Special Capital Region of Jakarta that connects three cities, South Jakarta City and East Jakarta City. Based on IRSMS (Integrated Road Safety Management System), data from the National Police showed increased traffic accident cases in MT. Haryono Gatot Subroto Street South Jakarta, where in 2019, there were 21 traffic accident cases. In 2020, there were 30 traffic accident cases, and in 2021, there were 38 traffic accident cases. This research method was descriptive, which describes current conditions using the Accident Rate method. This study aims to determine the level of traffic accidents on MT Haryono - Gatot Subroto Street, South Jakarta, to know the factors that cause accidents, and to find the black site area on MT. Haryono - Gatot Subroto Street South Jakarta, and to provide alternatives and solutions for prevention and management in reducing traffic accidents. This research shows that the black site area was on Gatot Subroto Street Segment 6, KM 5+500 – KM 6+500, with an accident rate of 6.33. The Blackspot identification was based on an accident rate of 0.27, and the black site identification was based on an accident rate of 0.27. The highest time of occurrence of traffic accidents was on Sunday at 03.00 – 04.00 WIB, so an actual speed survey was implemented at that time. The primary cause of traffic accidents based on POLRI IRSMS data was the human factor as drivers who are negligent and undisciplined in driving. An example of the causal factors found during the survey was drivers driving over the maximum speed limit—the alternatives and solutions for prevention and countermeasures in reducing traffic accidents on MT. Haryono-Gatot Subroto Street South Jakarta provides adequate lighting along the way and adds traffic signs before black site areas.